ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT STATE-OWNED BANKS OF SINJAI BRANCH - Annisa Nawawi; Andi Reni; Andi Bau Massepe (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to determine the effect of product quality on customer satisfaction, service quality on customer satisfaction, customer satisfaction on customer loyalty, product quality on customer loyalty, service quality on customer loyalty, product quality on customer loyalty through customer satisfaction, service quality on customer loyalty through customer satisfaction. This research includes a quantitative descriptive study with conclusions through statistical analysis. The population in this study were customers of State-Owned Banks of Sinjai Branch. The samples were taken as many as 100 customers based on the Slovin formula with proportional stratified random sampling technique. Data was collected through questionnaires and documentation and analyzed through validity, reliability, classic assumption test, path analysis, and Sobel test. The results of the analysis obtain a regression line equation: Z = 2.443 + 0.972X1 + 0.072X2 and Y = -0.3395 + 0.505X1 + 0.085X2 + 0.596Z. The equation shows that customer loyalty is influenced by the product quality and service quality through customer satisfaction. The results showed that product quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant on customer loyalty, product quality has a positive effect and there are significant customer loyalties, service quality has a positive and significant effect on customer loyalty, product quality has a positive and significant effect on customer loyalty if through customer satisfaction. customer loyalty through customer satisfaction at state-owned banks Sinjai Branch.